Report on ticks collected in the Southeast and Mid-West regions of Brazil: analyzing the potential transmission of tick-borne pathogens to man - Figueiredo, Luiz Tadeu Moraes; Badra, Soraya Jabur; Pereira, Luiz Eloy; Szabó, Matias Pablo Juan [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 1999)
Foram coletados espécimes de carrapatos em 1993, 1996, 1997, e 1998, principalmente de animais selvagens e domésticos, nas Regiões Sudeste e Centro-oeste do Brasil. Nove espécies de Amblyommidae foram identificadas: Anocentor Nitens, Amblyomma cajennense, Amblyomma ovale, Amblyomma fulvum, Amblyomma striatum, Amblyomma rotundatum, Boophilus microplus, Boophilus annulatus e Rhipicephalus sanguineus. Analisou-se o potencial destas nove espécies de carrapatos como transmissores de patógenos para o homem. Um Flaviviridade Flavivirus foi isolado de espécimes de Amblyomma cajennense coletados de um capivara doente (Hydrochaeris hydrochaeris). Amblyomma cajennense é o transmissor principal da Rickettsia rickettsii (=R. rickettsi), o agente causador da febre maculosa no Brasil. Os mamíferos selvagens, principalmente capivaras e veados infestados por carrapatos vivem em próximo contato com gado, cavalos e cachorros, com quem compartilham os mesmos carrapatos, oferecendo risco de transmissão destas zoonoses silvestres aos animais domésticos e ao homem.

Specimens of ticks were collected in 1993, 1996, 1997, and 1998, mostly from wild and domestic animals in the Southeast and Mid-West regions of Brazil. Nine species of Amblyommidae were identified: Anocentor nitens, Amblyomma cajennense, Amblyomma ovale, Amblyomma fulvum, Amblyomma striatum, Amblyomma rotundatum, Boophilus microplus, Boophilus annulatus, and Rhipicephalus sanguineus. The potential of these tick species as transmitters of pathogens to man was analyzed. A Flaviviridade Flavivirus was isolated from Amblyomma cajennense specimens collected from a sick capybara (Hydrochaeris hydrochaeris). Amblyomma cajennense is the main transmitter of Rickettsia rickettsii (=R. rickettsi), the causative agent of spotted fever in Brazil. Wild mammals, mainly capybaras and deer, infested by ticks and living in close contact with cattle, horses and dogs, offer the risk of transmission of wild zoonosis to these domestic animals and to man.
Relato sobre carrapatos coletados no Sudoeste e no Centro-oeste do Brasil analisando a potencial transmissão de microorganismos de carrapatos para o homem
Keywords: Carrapatos brasileiros; Patógenos transmitidos por carrapatos; Brazilian ticks; Tick-borne pathogens